A qualitative evaluation of a simplified cardiovascular management program in Tibet, China - Maoyi Tian; Xuejun Yin; Danzeng Dunzhu; Zhong Liu; Cong Li; Hao Sun; Ci Song; Laba Sangzhu; Anushka Patel; Julie Redfern; Lijing L. Yan (BMC, 2018)
Abstract Background The simplified cardiovascular management (SimCard Study) program was a cluster randomized controlled trial conducted in Tibet, China to evaluate a multifaceted intervention consisting of appropriate medication prescriptions and lifestyle recommendations delivered by village doctors. The intervention was effective in improving the management of cardiovascular diseases in resource-limited settings. The aim of this qualitative study was to examine stakeholder feedback and to inform future research and scaling up. Method A total of 28 face-to-face individual interviews were conducted. The interviews were conducted in 6 out of 14 intervention villages by 2 interviewers who speak the local language. Participants included 18 community members at high risk of CVD, 6 village doctors, 2 local project coordinators, and 2 county officials. Interview guides were used to facilitate the interview covering the focus of perceived usefulness and content of the intervention, fidelity to the intervention, and potential scalability of the intervention. Qualitative interviews were coded using thematic analysis. Results The average age of the participants was 41 years and 70% were female. Our findings showed that the intervention was delivered according to the protocol and was described as a useful program for CVD management by both high-risk individuals and village doctors. However, lack of knowledge among high-risk individuals, insufficient availability of healthcare providers, inadequate financial incentive, and incomplete infrastructure such as difficulty in transportation and cell phone signal were identified as the main barriers to successful implementation and scale-up. Conclusion The intervention was implemented in line with the protocol and provided substantial benefits for relevant community members and health professionals. However, multiple health system barriers need to be addressed for successful scale-up in rural China. Trial registration Unique identifier: NCT01503814. Registered 11 December 2011.